Does capital adequacy ratio influence risk-taking behaviour of conventional and Islamic banks differently? Empirical evidence from dual banking system of Malaysia - Harkati, Rafik; Alhabshi, Syed Musa; Kassim, Salina (Emerald Group Publishing Ltd., 2020)
Purpose – The purpose of this study is to investigate the influence of capital adequacy ratio (CAR) prescribed in Basel III on the risk-taking behaviour of Islamic and conventional commercial banks in Malaysia. It also investigates the claim that the risk-taking behaviour of Islamic banks (IBs) and conventional banks (CBs) managers is identically influenced by CAR. Design/methodology/approach – Secondary data for all CBs operating in the Malaysian banking sector are gathered from FitchConnect database for the 2011–2017 period. Both dynamic ordinary least squares and generalised method of moments techniques are used to estimate a panel data of 43 commercial banks, namely, 17 IBs and 26 CBs. Findings – The findings of this study lend support to the favourable influence of CAR set in Basel III accord on risk-taking behaviour of both types of banks. CBs appeared to be remarkably better off in terms of capital buffers. Evidence is established on the identicality of the risk-taking behaviour of IBs and CBs managers under CAR influence. Practical implications – Even though a high CAR is observed to hamper risk-taking of banks, the findings may serve as a signal to regulators to be mindful of the implications of holding a high CAR. Similarly, managers may capitalise on the findings in terms of strategising for efficient use of the considerable capital buffers. Shareholders are also concerned about managers’ use of the considerable capital buffers. Originality/value – This study is among a few studies that endeavoured to provide empirical evidence on the claim that IBs mimic the conduct of CBs in light of the influence of CAR prescribed in Basel III on risktaking behaviour, particularly banks operating within the same banking environment.